Application of sampled-data control by using vibration manipulation function to suppress residual vibration of travelling crane - Shigeo KOTAKE (The Japan Society of Mechanical Engineers, 2015)
Vibration manipulation function (VMF) is applied as a linear-piecewise feedforward function to suppress residual vibration of a hoisting load in a one-dimensional overhead travelling crane. The system is modeled as a pendulum of a one-degree-of-freedom (1DOF) oscillator with enforced acceleration of a trolley. When an initial swing angle of the wire of the crane is small, residual vibration of the load can be vanished by this method in one natural period of the oscillator. On the contrary, in case of a large initial angle, certain amount of residual vibration remains because of the nonlinearity of the pendulum. However, it can be eliminated with repeated enforce accelerations of the trolley under VMF in every natural period. Moreover, in case of the existence of external noises and errors, the intermittent repeated accelerations can remove residual vibration with sampled-data feedback control in every natural period. Some examples of numerical simulations and experimental results are shown to validate the abilities of VMF in the crane operation. Residual vibration of the load can be suppressed in any time of the crane work, as far as the trolley travels in constant speed including static position, i.e. in any inertial frame, at the beginning of each operation. This feedforward function could be used for an automatic crane machine with or without the sampled-data feedback control. Since the function is an analytic solution of an intrinsic repowering operations, it can also be used in tutoring software for operator's training.